USE OF BUDGET FUNDS BY RUSSIAN ECONOMIC ENTITIES: ANALYSIS AND MONITORING CRITERIA - Petrov A.M.; Sembiyeva L.M.; Kuzmina A.A.; Markova O.M. (Scientific Journal of Pedagogy and Economics, 2020)
Efficient utilization of the budget funds provided by the government for development is ensured by applying the result-driven program-based method of planning or budgeting. This method enables rational distribution of the available country’s resources for solution of medium- and long-term problems related to economic, social, and environmental development in order to makes the most of the investments by implementing designated programs. Efficient use of budgetary funds is a successful tool of national development. A number of designated national, federal, and departmental programs have been implemented at the federal level of the Russian Federation. A targeted federal investment program has been in operation. Despite the number of the development programs, the federal designated programs are prioritized and take a central position in the general structure of the implemented programs. Their priority is defined by focusing on development of an integrated and comprehensive approach for elaboration of measures aimed at meeting the objectives and integration of the activities of universities, scientific organizations, and economic entities of the economic development sector. The field of small and medium-sized entrepreneurship (SMSE) is prioritized upon implementing federal, national, and departmental designated programs. The Russian Federation field of small and medium-sized entrepreneurship is represented by legal entities and individual entrepreneurs grouped into three categories – micro, small, and medium. Implementation of the national development programs facilitates increase of the financial standing level of the economic entity, which implements such programs. On the other hand, financial standing is an economic-activity indicator of the economic entities pertaining to various business areas as the financial standing level is representative of the financial resource capacity required for smooth operation and reasonable allocation of resources, as well as of the efficiency of resources utilization by an economic entity.